ATM Functions at the Peroxisome to Induce Pexophagy in Response to ROS - Zhang, Jiangwei (Nat Cell Biol, 2015)
Peroxisomes are highly metabolic, autonomously replicating organelles that generate ROS as a by product of fatty acid β-oxidation. Consequently, cells must maintain peroxisome homeostasis, or risk pathologies associated with too few peroxisomes, such as peroxisome biogenesis disorders, or too many peroxisomes, inducing oxidative damage and promoting diseases such as cancer. We report that the PEX5 peroxisome import receptor binds ataxia-telangiectasia mutated (ATM) and localizes this kinase to the peroxisome. In response to reactive oxygen species (ROS), ATM signaling activates ULK1 and inhibits mTORC1 to induce autophagy. Specificity for autophagy of peroxisomes (pexophagy) is provided by ATM phosphorylation of PEX5 at Ser141, which promotes PEX5 mono-ubiquitination at K209, and recognition of ubiquitinated PEX5 by the autophagy adapter protein p62, directing the autophagosome to peroxisomes to induce pexophagy. These data reveal an important new role for ATM in metabolism as a sensor of ROS that regulates pexophagy.